Advanced Control for Mineral Processing: Better Than Expert Systems - Robert K. Jonas (Canadian Institute of Mining, Metallurgy and Petroleum, 2008)
"Minerals processors can improve production by using the best available control technology to control their operations. Many mines use expert systems that can provide improved results over manual or basic control, but better results can be achieved using multivariable predictive control. Over the past few years, the application of multivariable predictive control has gained acceptance in many mining processes and has recently proven to be suitable for some of the most challenging processes. This advanced control technology has been successfully applied to a wide variety of processes; alumina digestion, ball mills, CCD/thickeners, kilns/calciners/roasters, heat exchangers/evaporators, and more demanding processes like SAG mills and flash smelters.This paper discusses the needs of advance control technologies in the mining industry, including the impact of these technologies on best practices for implementation and long term sustainability. Results of the multivariable predictive control applications in mineral processing are discussed, and in particular the application to the SAG mill. In addition, an example of the benefits improvement that can be achieved with this technology is presented.INTRODUCTIONThere has been a long term perception in the mainstream mineral processing industry that best advanced control solution is an expert system. There a numerous instances of expert systems used for control of SAG mills, as well as kilns or roasters, thickeners and more recently flotation circuits. Many of theses expert systems have been installed by small, independent companies or by OEMs of processing equipment. Undoubtedly these expert systems have provided millions in benefits to the owners of mineral processing plants.It is this author’s proposition that it is a misconception to believe that expert systems are the best solution for mineral processors, and that in many cases the best solution is Multivariable Predictive Control (MPC). Better control and optimal operations can be achieved through the use of MPC. Another important consideration when considering advanced control technologies is the implementation and support effort. These types of applications have been known to deteriorate, even to disuse, when they are not kept up to date with changes to the process or equipment. The audience is invited to listen to discussion and draw their own opinion. The author has been involved in installing control systems for over 20 years, advanced solutions for over 15 years, and has had privilege to consult with many miners concerning the selection and application of advanced controls over the past 6 years."